Transient expression of VP2 in Nicotiana benthamiana and its use as a plant-based vaccine against Infectious Bursal Disease Virus - Gomez, Evangelina Raquel; Lucero, Maria Soledad; Chimeno Zoth, Silvina Andrea; Carballeda, Juan Manuel; Gravisaco, María José; Berinstein, Analia (Elsevier, 2019)
Infectious Bursal Disease Virus (IBDV) is the etiological agent of an immunosuppressive and highly contagious disease that affects young birds. This disease causes important economic losses in the poultry industry worldwide. The VP2 protein has been used for the development of subunit vaccines in a variety of heterologous platforms. In this context, the aim of this study was to investigate VP2 expression and immunogenicity using an experimental plant-based vaccine against IBDV. We determined that the agroinfiltration of N. benthamiana leaves allowed the production of VP2 with no apparent change on its conformational epitopes. Chickens intramuscularly immunized in a dose/boost scheme with crude concentrated extracts developed a specific humoral response with viral neutralizing ability. Given these results, it seems plausible for a plant-based vaccine to have a niche in the veterinary field. Thus, plants can be an adequate system of choice to produce immunogens against IBDV.